Cantilever Beam Framing Systems - Hemstad, Michael (Engineering Journal, 1999)
Cantilever beam framing is a multiple-span system of framing which is more efficient than simple beam framing, but simpler to design and erect than continuous beam systems. It involves cantilevering the beam from one span past a support a short distance into the next span, where it supports the end of the next beam using a simple shear connection. This is shown in Figure 1 for two-span and three-span configurations. The configurations are identified as SC (suspended span/cantilever), CSC (cantilever/suspended span/cantilever), and SCS (suspended span/cantilever/suspended span). Cantilever framing systems are a reasonable and economical alternative to simple span and continuous beam framing systems. While more demanding analytically than simple span framing, in buildings with large bays they will typically be the most economical system available. In large buildings with regular repetitive layouts, this additional design effort is offset by the construction savings realized. Using the simplified methods and equations described in this paper, these systems are viable for many routine designs.